Annotated zoogeography of non-marine Tardigrada. Part IV: Africa - Mcinnes, Sandra J.; Michalczyk, Łukasz; Kaczmarek, Łukasz (Zootaxa, 2017)
This paper is the fourth monograph in a series that describes the global records of limno-terrestrial water bears (Tardigrada). Here, we provide a comprehensive list of non-marine tardigrades recorded from Africa, providing an updated and revised taxonomy accompanied by geographic co-ordinates, habitat, and biogeographic comments. It is hoped this work will serve as a reference point and background for further zoogeographical and taxonomical studies.